A fresh look at the intervention logic of Structural Funds. (April 2013) - Gaffey, Veronica
In the 1990s, the European Commission initiated the MEANS programme of evaluation guidance for socio-economic programmes, primarily for those co-financed with the Structural Funds. This initiative developed an intervention logic that has remained in place ever since. The Directorate General for Regional and Urban Policy has recently been taking a fresh look at the logical framework. We have examined it drawing on experiences from three programming periods: from the perspective of an intensive ex post evaluation of the 2000–06 programming period; from the perspective of reporting on the ongoing performance of current programmes; and from the perspective of designing a policy for 2014–20 with a stronger result orientation. The conclusion of this work is that our intervention logic was never entirely clear. We cannot in practice distinguish between a short-term direct effect (result) and a longer-term, indirect effect (impact). We have never actually measured impacts defined like this. With the increasing focus on outcomes in the international literature and the developments concerning the evaluation of impact – defined as the 'change that can credibly be attributed to an intervention', we realize that we need to clarify our intervention logic. This article outlines the experiences of the Directorate General for Regional and Urban Policy and its proposals for a re-articulation of the logic of our interventions and the terminology we use in this regard.